PENGARUHRASIO AKTIVITAS TERHADAP KINERJA KEUANGAN PADAPERUSAHAAN FOOD AND BEVERAGES YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Nala Syakhiya (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2020)
The food and beverage industry is one of the industrial categories on the IDX that has opportunities to growth and developed. This can be seen from the number of companies listed on the IDX from time to time. Most likely this company is very needed by society that will provide benefits both now and which will come.The purpose of this study was to determine the effect of Total Asset Turnover, Inventory Turnover, and Receivable Turnover on Return On Asset in Food and Beverages on the Indonesia Stock Exchange. This type of research is associative. The method used is multiple panel linear regression analysis with the help of the Eviews10 program. The population in this study is the Food and Beverages Companies listed on the Indonesia Stock Exchange in the 2014-2018 period, amounting to 15 companies. The sample in this study were 5 companies. The results showed that the activity ratio consisting of total asset turover, inventory turnover, and receivable turnover had a positive and significant effect in financial performance as measured by return on asset.